Teoria crítica e religião: uma leitura da religião em Adorno e Horkheimer - Sousa, José Rogério Gomes de (2016)
The present work aims to address argumentative religion in the perspective of two Frankfurt School theorists: Theodor w. Adorno and Max Horkheimer. To understanding the religion in such authors do if necessary against the backdrop of critical theory. It is worth mentioning that there is a theory of religion in the Frankfurt School, but that religion consists of a part that is embedded in the study done by the Frankfurt School theorists. Critical theory attempts to do an analysis of society at large, which appears in theoretical studies. So, religion is understood as an integral part of society and should not be excluded from research. Religion understood from the bias of critical theory gives the possibility to seize his conjecture in both society and the daily life of each individual. There is, therefore, an imperative that is outside the scope in which commonly religion is entrenched: maybe, that religion would be free of ideology and of a teleological usage for certain purposes. In the course of argumentative text, in the first time you do a brief approach to the historical context in which the Frankfurt School is embedded. This context will make it possible to understand the development of critical theory. In the second, covers about religion and for such a venture be used two theoretical perspective: Max Horkheimer, with their proposal to understand religion as critical instance with the intention to safeguard the subject and Theodor Adorno that rooted on the issue nazifascista and anti-Semitism understand religion as a way to recover the lost hope. From this theoretical duplicitous if attempts to understand the importance of discussing religion under the Frankfurt School. Perhaps a reading that is not on the edges of the only obvious, but that enters in the nitty-gritty and conjecture.